Analisis Mood Mahasiswa dalam Satu Minggu Menggunakan Statistik Deskriptif dan Korelasi Spearman - Nurhayati; Regina Ramadhani; Risma Nur Indriyani; Perani Rosyani (CV. Multi Kreasi Media, 2025)
This study aims to analyze fluctuations in student mood over the course of one week and to identify factors associated with these changes using descriptive statistics and Spearman correlation. A total of 49 students from the Informatics Engineering program were selected using the Slovin formula. Data were collected through a daily questionnaire measuring mood, energy level, sleep quality, mood-influencing factors, and the impact of mood on learning concentration. Descriptive results indicate that student mood varies throughout the week, with the lowest level occurring on Monday and the highest on Saturday. Spearman correlation analysis reveals a strong and significant positive relationship between mood and both energy level (ρ = 0.558) and learning concentration (ρ = 0.560). In contrast, sleep quality shows a weak and non-significant relationship with mood. These findings indicate that internal conditions such as energy and concentration have a greater influence on daily mood than sleep quality. The study provides valuable insights into students’ emotional dynamics and highlights key factors that may support academic well-being.